Widom Factors and Szegő–Widom Asymptotics, a Review - Christiansen, Jacob S.; Simon, Barry; Zinchenko, Maxim (Operator Theory: Advances and Applications, 2022)
We survey results on Chebyshev polynomials centered around the work of H. Widom. In particular, we discuss asymptotics of the polynomials and their norms and general upper and lower bounds for the norms. Several open problems are also presented.
Publisher Copyright: © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Chebyshev polynomials; Szegő–Widom asymptotics; Totik–Widom upper bound; Widom factors